Knowledge and Practices of Mothers Regarding Food Safety Presenting to Family Medicine Clinics at a Teaching Hospital in Karachi Pakistan - Veena Kumari Harani , Marie Andrades , Anum Arshad Beg , Zainab Mohammad , Mahadev Harani (Journal of Rawalpindi Medical College, 2018)
Background:.To assess the knowledge and practices of mothers regarding food safety presenting to family medicine clinics of a teaching hospital in Karachi, Pakistan. Methods: In this cross sectional study 240 mothers, having children under five years of age, were selected through non probability consecutive sampling. A pretested structured questionnaire on knowledge and practices of food safety was used with face-to-face interviews. Results:Adequate knowledge was found in 82.5% and correct practices in 75.8% of mothers. Frequency of adequate knowledge and correct practices were more among those with higher education (p=0.028 and p= 0.001) respectively. Factors significantly associated with practices regarding food safety were age (OR: 0.57, 95% CI: 0.312-1.04) and education. (OR: 0.178, 95% CI: 0.02-1.1). Most of the mothers were 25-30 years of age(37.9%). Most of the mothers (83.8%) were housewives. Majority (69.2%) have completed higher education. Food ingredients ,before purchasing, were checked by 44.6%,while 34.2% tasted food by fingers. Only 55.4% knew that boiled water is safe for drinking and cooking purposes. Conclusion: Inadequate knowledge regarding food safety was seen in 17.5% mothers and 24.2% have incorrect practices regarding food safety,which is significant.